Role of the Truview EVO2 laryngoscope in the airway management of elective surgical patients: A comparison with the Macintosh laryngoscope - Saxena, Arpita (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: The Truview EVO2(C) laryngoscope (TL) is a recently introduced optical device designed to provide an unmagnified anterior image of the glottic opening and allow indirect laryngoscopy. AIM: This study is designed to determine whether the TL is a better alternative to the Macintosh laryngoscope (ML) for routine endotracheal intubations in patients with usual airway characteristics. METHODS: We compared the Truview EVO2(C) and MLs in 140 elective surgical patients requiring general anaesthesia and intubation in a prospective crossover fashion. The two blades were compared in terms of Cormack and Lehane grades, time required for intubation, anaesthetists’ assessment of ease of intubation, intubation difficulty score, attempts at intubation, success rate, soft tissue damage and arterial oxygen saturation during laryngoscopy. The Student t test and Chi-square test were used to determine the statistical significance of parametric data and categorical data, respectively. RESULTS: The Truview EVO2(C) blade provided a better laryngoscopic view than the Macintosh blade as suggested by improved Cormack and Lehane grades (in 48 patients), but required a longer time for intubation than the Macintosh blade (34.1 vs. 22.4 s), i.e., an improved view at the cost of longer mean intubation time. In spite of lower intubation difficulty scores, Truview EVO2(C) was considered as difficult to use on subjective assessment by the anaesthesiologist when compared with Macintosh. There was no difference observed between the two groups in attempts at intubation, success rate, soft tissue damage and arterial oxygen saturation during laryngoscopy. CONCLUSION: We opine that although Truview provides a better laryngoscopic view than Macintosh in difficult cases, it does not have an extra benefit over Macintosh otherwise, further indicating the need for more experience with the use of a Truview laryngoscope.